(3GdGbJUGO GdSjGSj dUfGOjb GdKQhI GdSjGOjIs - (3HdbGSe(B, (3RGjQjs ((3GdLRGFQ (B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2020)
(3JfGhd GdcGJH ehVhY UfGOjb GdKQhI GdSjGOjI hJMhdGJ GdfXGe GdeGdj GdOhdj, MjK bOe ef NdGd aUhd OQGSJg UfGOjb GdKQhI GdSjGOjI hETcGdjI Gdeaghe, h CgOGa GdSjGSGJ GdeYJeOI ef WQa UfGOjb GdKQhI GdSjGOjI, HGdGVGaI Gdi GdJejjR Hjf UfGOjb GdKQhI GdSjGOjI hGdcjGfGJ GdeGdjI hGdGSJKeGQjI GdCNQi, hCNjQG Sdhc hGSJQGJjLjI UfGOjb GdKQhI GdSjGOjI aj EOGQI GdCUhd(B.s
(3GdeQGLY U(B.275 (3bGFeI HCSeGA UfGOjb GdKQhI GdSjGOjI U(B.11s
Keywords: (3GdGbJUGO GdSjGSjs; (3GdfXGe GdfbOj GdOhdjs